MODERN APPROACHES TO DIAGNOSIS AND TREATMENT OF PATIENTS WITH RESPIRATORY TRACT BURNS - I.B, Mustafakulov; A.U, Ziyodullaev; Z.A, Jurayeva (Research Focus International Scientific Journal, 2026)
Respiratory tract burns remain one of the most complex and pressing issues in clinical burn medicine, significantly worsening the course of burn disease and increasing mortality. This paper presents the results of an analysis of the diagnosis and treatment of patients with respiratory tract burns based on clinical, laboratory, and endoscopic examination methods. It has been established that fiberoptic bronchoscopy combined with cytological examination of bronchoalveolar fluid is the most informative method for diagnosing respiratory tract damage. The developed approach to assessing the severity of damage allows for the optimization of treatment strategies and improved patient outcomes.